TLR4 May Be Involved in the Regulation of Colonic Mucosal Microbiota by Vitamin A - Xiao, Lu; Chen, Baolin; Feng, Di; Yang, Ting; Li, Tingyu; Chen, Jie (Frontiers in Microbiology, 2019)
Abstract Objectives: To investigate the specific role of TLR4 in the regulation of the intestinal mucosa-associated flora by vitamin A (VA). Methods: Both TLR4-/- (KO) and wild-type (WT) female mice were randomly fed a VA normal (VAN) or VA deficiency (VAD) diet for 4 weeks to establish the following four mouse model groups: TLR4-/- mice fed a VAN diet (KO VAN), TLR4-/- mice fed a VAD diet (KO VAD), WT mice fed a VAN diet (WT VAN), and WT mice fed a VAD diet (WT VAD) . Then, the female mice from each experimental group were mated with male mice with the same genetic background. The pups in the KO VAD and WT VAD groups were subsequently fed the VAD diet after weaning, while the pups in the KO VAN and WT VAN groups were fed the VAN diet continuously after weaning. The serum retinol levels of 7-week-old offspring were determined using high-performance liquid chromatography, and the colons from each group of mice were collected and analyzed by using an Illumina MiSeq platform for 16S rRNA gene sequencing to characterize the overall microbiota of the samples. Results: The abundance and evenness of the colon mucosa-associated microflora were unaffected by dietary VA and TLR4-/-. VAD decreased the abundances of Anaerotruncus (Firmicutes), Oscillibacter (Firmicutes), Lachnospiraceae _NK4A136 _group (Firmicutes) and Mucispirillum (Deferribacteres) and increased the abundance of Parasutterella (Proteobacteria). TLR4-/- decreased the abundances of Bacteroides (Bacteroidetes) and Alloprevotella (Bacteroidetes). However, the abundances of Allobaculum (Firmicutes), Ruminiclostridium_9 (Firmicutes), Alistipes (Bacteroidetes) and Rikenellaceae_RC9 (Bacteroidetes) impacted the interaction between VA and TLR4. Conclusions: TLR4 may play a pivotal role in the regulation of the intestinal mucosa-associated flora by VA to maintain the intestinal microecology.